2019
DOI: 10.1111/os.12549
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Evaluation of Patellofemoral Instability: A Clinical Reality or Just a Research Field? A Literature review

Abstract: Patellofemoral instability (PFI) is one of the most disabling conditions in the knee, often affecting young individuals. Despite its not uncommon presentation, the underlying biomechanical features leading to this entity are not entirely understood. The suitability of classic physical examination manoeuvres and imaging tests is a matter of discussion among treating surgeons, and so are the findings provided by these means. A potential cause for this lack of consensus is the fact that, classically, the diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…17 Nevertheless, the focus of the present study was to explore other potential factors that may influence the outcomes of isolated MPFLR rather than the technique per se. Fourth, the stability of the patella and knee function depend on static and dynamic structures 28 -for example, the quadriceps, especially the internal oblique muscle. The study did not take this factor into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…17 Nevertheless, the focus of the present study was to explore other potential factors that may influence the outcomes of isolated MPFLR rather than the technique per se. Fourth, the stability of the patella and knee function depend on static and dynamic structures 28 -for example, the quadriceps, especially the internal oblique muscle. The study did not take this factor into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Although both TT-TG and TT-PCL can be used to assess patellar alignment, an increased TT-PCL value represents true tibial tubercle lateralization 33 . In addition to dynamic CT 35 , dynamic MRI may be used to assess patellar maltracking. A recent study found that in patients with maltracking, a greater degree of mediolateral translation (12.4 ± 6.9 mm vs. −0.1 ± 2.3 mm) and a more lateral position of the patella were present compared with controls.…”
Section: Imagingmentioning
confidence: 99%
“…In order to diagnose subject-specific knee kinematics and pathologies, several in-vivo dynamic imaging techniques of the knee joint have been developed using a variety of different modalities such as MRI, Fluoroscopy, CT or a combination of these techniques [1,2]. In these studies various loading conditions and dynamic tasks were investigated [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In two comprehensive review studies, the current state of dynamic imaging for the patellofemoral joint was studied [2,8]. Both review studies conclude that dynamic imaging provides valuable insight into knee kinematics and pathologies and underline the need for objective and accurate determination of subject-specific knee kinematics.…”
Section: Introductionmentioning
confidence: 99%